Leadership styles of secondary school administrators : basis for a leadership guide - Cristobal, Cristobal P. (San Carlos City, Pangasinan : [s.n.], 2015)
This study sought to analyze the secondary school administrators' profile and their leadership styles. It also aimed to find out the association between the profile of the school administrators and their leadership styles as basis for the leadership guide. Findings revealed that, more females served as school administrators. Most administrators were married and that most them were holders of masteral units. As to length of service, most of the administrators were in their respected posts for many years. As to leadership styles, democratic and servant leadership were always used by school administrators. It is concluded that most of the school adminstrators are in their middle age. Most of them have not had district and international seminars. The leadership style which was not prominent among administrators was on laissez-faire specifically on delegating task to followers even without direction, allowing followers to have complete freedom to make decisions concerning the completion of their work and full rights and powers of followers in decision-making. The young administrators seemingly opt for transformational leadership especially on making change and directing the thinking of followers to change and inspire others to work. They so would like to create vision of what they would like to aspire and want to take risk and irregular strategies. The leadership guide of the secondary school administrator could be of big help in their management. It is recommended that administrators must join comprehensive trainings and have leadership guide such as the one proposed in this study. They have to strengthen their professional bearing associated with leadership by of finishing their masteral and doctoral degrees. They have to develop a culture in delegating tasks to followers even without direction, allowing followers to have complete freedom to make decisions concerning the completion of their work and full rights and powers of followers in decision-making through an intensive leadership workshop. More international seminars have to be espoused for the secondary school administrators by building affinities with leadership-centered organizations. Secondary school administrators have to vary their leadership styles depending on situations they meet.
Bibliography: pages 104-105.
CHED-La Union
Keywords: Teachers -- Leadership